PERAN GURU MADRASAH DALAM MENANAMAN NILAI-NILAI PENDIDIKAN LINGKUNGAN HIDUP PERSPEKTIF PENDIDIKAN ISLAM (STUDI KASUS DI MADRASAH ALIYAH NEGERI 7 KEBOAN JOMBANG) - Auliyaaurohmah, Auliyaaurohmah; Umam, Khoirul (Universitas Ahmad Dahlan, 2020)
The effort to preserve the beauty of the environment is an obligation for every social creature that lives on this earth. These efforts are carried out and planned so that every human being has a caring attitude and responsibility with the surrounding environment. In educational institutions the role of a teacher cannot be separated in the educational process. To realize students as quality resources cannot be separated from the environment. This article intends to explain about environmental education in Madrasah Aliyah Negeri 7 Jombang. With a qualitative case study approach, this research was carried out through observation, interviews and documentation. The results of the discussion from the research show that, in the implementation of their roles and participation in forming and increasing environmental awareness by teachers, students are well implemented. Most of them have a caring attitude to their environment, which is proven by their daily habits, which is to dispose of waste according to the space provided. It's just that for minorities who are still indifferent to the environment, support and encouragement from teachers need to be increased so that all madrasa residents, especially students, have positive behavior, be aware and care about the surrounding environmen